IMPLEMENTATION OF ARABIC LANGUAGE LEARNING IN MADRASAH TSANAWIYAH IN PONDOK AL-QUR'AN AL-MAJDIYAH BAGAN BATU RIAU - Utami, Noviza Elanda (Yayasan Haiah Nusratul Islam, Indonesia, 2024)
This research was conducted at Pondok Al-Qur'an Al-Majidiyah Bagan Batu, with a qualitative research approach. Research data collection was obtained through observation, interviews and documentation studies. This research aims: 1. To find out how the implementation of Arabic language learning madrasah tsanawiyah, 2. to find out what methods are used in the implementation of Arabic language learning. From the results of research conducted by the author, it can be concluded that: First, The implementation of Arabic language learning used is Bruner's Learning Steps. These steps are very suitable for the beginner level, according to the background of students who are still basic; Second, In the method of Arabic Language Learning at Pondok Al-Qur'an Al-Majidiyah Bagan Batu in this year has been effective The method used by the teacher in the implementation of learning takes place using in the essay of Ulin nuha,.Variety of methodologies and media for learning Arabic Classical or group teaching methods, and individual teaching methods .although in the learning process in the classroom is not optimal students can still speak with correct Arabic and at least lacking in the attention and motivation given by the teacher.